Dietary supplements and fortified foods - Zeisel, Steven H.; Kohlmeier, Martin; Cooksey, Karen; Plaisted, Claudia; Kelly Adams (2002)
Teaches how to evaluate dietary supplements and other components in order to provide advice to patients
Narrator: Mike Urben
System requirements: Pentium CPU / 200 MHz processor; 32 MB RAM; Windows 95/98/NT or later; quad speed CD-ROM drive; sd. card; monitor with screen resolution of 640 x 480, capable of running high color (16-bit); QuickTime 3.0 or higer.
Keywords: Dietry supplements; Food, Fortified; Nutrition